Analysis of the status and proposals for the development of road infrastructure in the region (Journal of Economic Research & Business Administration, 2015)
At the present stage of society development the issues of functioning of the transport infrastructure are becoming increasingly topical. Raising the competitiveness of national economy, regions and industries cannot be isolated from the full realization of transit potential, which, in its turn, is based on an extensive, available, high quality and efficientinfrastructure. Since the 90's road transport in Kazakhstan grew rapidly and currently is in second place (after the railway and pipeline), covering over 20% of freight and 90% of passenger traffic. Ensuring of sustainable development, improving of investment climate, increasing of competitiveness of the national economy, creating conditions for Kazakhstan's to transit to innovative development, stimulating of regional development is largely dependent on the availability and quality of infrastructure, road network being an important component here. Currently the road infrastructure is backward the needs of society, that resulted from unbalanced growth of autopark and financing of theindustry.
Keywords: road infrastructure; economic effects; economic development; social effects; regional development; transport policy